2012
DOI: 10.1093/brain/aws004
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of frontotemporal dementia and/or amyotrophic lateral sclerosis associated with the GGGGCC repeat expansion in C9ORF72

Abstract: Numerous kindreds with familial frontotemporal dementia and/or amyotrophic lateral sclerosis have been linked to chromosome 9, and an expansion of the GGGGCC hexanucleotide repeat in the non-coding region of chromosome 9 open reading frame 72 has recently been identified as the pathogenic mechanism. We describe the key characteristics in the probands and their affected relatives who have been evaluated at Mayo Clinic Rochester or Mayo Clinic Florida in whom the hexanucleotide repeat expansion were found. Forty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

31
293
1
16

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 323 publications
(341 citation statements)
references
References 67 publications
31
293
1
16
Order By: Relevance
“…These data reveal vulnerable neuroanatomical structures during the presymptomatic and symptomatic stages, which include ventral and dorsomedial prefrontal cortex, ventral and dorsal insula, anterior cingulate, caudate, and the medial thalamus. These regions are highly anatomically congruent with atrophy patterns found in C9orf72 ‐associated frontotemporal dementia 45, 47, 48, 49, 50. Notably, several studies confirmed that the medial thalamus is a region affected across C9orf72 expansion carriers,50 even during the presymptomatic phase 23, 36, 46.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…These data reveal vulnerable neuroanatomical structures during the presymptomatic and symptomatic stages, which include ventral and dorsomedial prefrontal cortex, ventral and dorsal insula, anterior cingulate, caudate, and the medial thalamus. These regions are highly anatomically congruent with atrophy patterns found in C9orf72 ‐associated frontotemporal dementia 45, 47, 48, 49, 50. Notably, several studies confirmed that the medial thalamus is a region affected across C9orf72 expansion carriers,50 even during the presymptomatic phase 23, 36, 46.…”
Section: Discussionsupporting
confidence: 66%
“…In parallel with the ROI analysis, the voxel‐wise analysis showed that certain sparse regions of lower grey matter volumes tended to associate with higher poly(GP), which included regions in the bilateral dorsolateral prefrontal, medial frontal, and lateral temporal cortices. Although higher poly(GP) levels showed a relatively weak association with lower grey matter volumes in our analyses, the regions identified include those atrophied in C9orf72‐ associated FTD patients,45, 47, 48, 49 and show reduced volume in presymptomatic C9orf72 expansion carriers 23, 36…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…In cohorts of patients with clinical diagnosis of FTD and C9ORF72 repeat expansions, the prevalence of psychosis ranges from 3 to 56 % compared to ∼4 to 14 % in non-carriers [5•, 11, 16-19]. Hallucinations occur in up to 50 % [20] and can include visual, auditory, and somatic. Delusions are present in up to 53 % [5•] and most commonly include paranoid, persecutory, or somatoform delusions.…”
Section: C9orf72 and Psychosismentioning
confidence: 99%
“…C9orf72 repeat expansions are involved with a wide spectrum of neurological manifestations 37,38 , involving motor and nonmotor (cognitive and behavioral) phenotypes (syndromes) 38 ( Figure 4). Most clinical data come from populational studies in European countries and in US.…”
Section: Clinical and Laboratory Characterizationmentioning
confidence: 99%